Quinhydrone Chemical Passivation of a Silicon Surface for Minority Carrier Bulk-Lifetime Measurements - M. Solcansky; J. Vanek; A. Poruba (International Journal of Photoenergy)
For the measurement of the minority carrier bulk-lifetime the characterization method MW-PCD is used, where the result of measurement is the effective carrier lifetime, which is very dependent on the surface recombination velocity and therefore on the quality of a silicon surface passivation. This work deals with an examination of a different solution types for the chemical passivation of a silicon surface. Various solutions are tested on silicon wafers for their consequent comparison. The main purpose is to find optimal solution, which suits the requirements of a time stability and start-up velocity of passivation, reproducibility of the measurements and a possibility of a perfect cleaning of a passivating solution remains from a silicon surface, so that the parameters of a measured silicon wafer will not worsen and there will not be any contamination of the other wafers series in the production after a repetitive return of the measured wafer into the production process. The cleaning process itself is also a subject of a development.